2017
DOI: 10.3892/ol.2017.6072
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the relative biological effectiveness and uniform isobiological killing effects of irradiation with a clinical carbon SOBP beam on DNA repair deficient CHO cells

Abstract: Abstract. Spread-out Bragg peak (SOBP) C ions have been used clinically in charged particle radiation therapy for years. An SOBP beam consists of various monoenergetic Bragg peaks; however, the biological effect of irradiation with an SOBP beam track has not been well-studied. In order to determine the clinically prospective molecular targets, radiosensitivity to the beam track in DNA repair deficient cell lines was investigated. A total of four distinct Chinese hamster ovary (CHO) cell lines, including CHO10B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The radiosensitivity of MG63 and MG63R was assessed by colony formation assay. This assay was carried out by using OptiCell culture chambers (Thermo Scientific) according to previous descriptions [ 16 ]. Cell culture medium containing 400–600 cells at a volume of 10 ml was added to each chamber.…”
Section: Methodsmentioning
confidence: 99%
“…The radiosensitivity of MG63 and MG63R was assessed by colony formation assay. This assay was carried out by using OptiCell culture chambers (Thermo Scientific) according to previous descriptions [ 16 ]. Cell culture medium containing 400–600 cells at a volume of 10 ml was added to each chamber.…”
Section: Methodsmentioning
confidence: 99%
“…The radiosensitivity of MG63 cells and MG63R cells was assessed by colony formation assay. This assay was carried out by using OptiCell culture chambers according to previous descriptions [ 14 ]. Cell culture medium containing 400–600 cells at a volume of 10 mL was added to each chamber.…”
Section: Methodsmentioning
confidence: 99%
“…When both PARP signaling and homologous recombination was inhibited, lung cancer and pancreatic cancer cells showed enhanced proton radiation-induced cell killing (171). For carbon ion irradiation, multiple in vitro studies have shown that the use of a PARP inhibitor can sensitize cancer cells to carbon ion irradiation (Table 3) (97,98,212). Interestingly, some of these studies showed that PARP inhibition has a higher radiosensitizing effect in combination with carbon ion radiation compared to photon irradiation (97,98,101).…”
Section: Inhibition Of Parpmentioning
confidence: 99%